The Politics of Emerging Strategic Technologies Implications for Geopolitics, Human Enhancement and Human Destiny - Al-Rodhan, Nayef R.F.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
Examines key trends in emerging strategic technologies and the implications for geopolitics and human dignity. Al-Rodhan argues that future evolution into transhumans is inevitable. In preparation, the global community is urged to establish strict moral and legal guidelines balancing innovation with the guarantee of dignity for all.
Keywords: Social justice; Human rights; Political theory; Political philosophy; Geography; Evolutionary biology; Political sociology; Social Justice, Equality and Human Rights; Political Theory; Political Philosophy; Geography, general; Evolutionary Biology; Political Sociology